Availability and Reliability Analysis of Magnetic Separators for Continuous Improvement - Coelho, John Márcio de Oliveira; Pereira, Natália Fernanda Santos; Barbosa, Lendro César Mol; Gamarano, Clárison Gonçalves; Sabará, Marco Antônio (Brazilian Journal of Production Engineering, 2023)
Due to the need for continuous improvement in order to reduce failures in magnetic separators in the mining concentration process, an analysis of the availability and reliability of these equipment (SM-A, SM-B, SM-C and SM-D) was carried out. Therefore, the research method was the descriptive case study, which consisted of carrying out quantitative analyzes of the maintenance indicators. In addition, the Pareto Diagram and FMEA tools were used for more assertive decision-making. Therefore, the MTTR, MTBF and Availability indicators were calculated from January 2021 to January 2023, in which availability values ​​were found for 98.03% for SM-A, 95.95% for SM-B, 97.31% for SM-C and 98.73% for SM-D. With the help of the ProConf2000 software, the Weibull distribution was modeled to calculate the reliability for a 360-hour mission, which obtained values ​​of 37.26%, 31.40%, 43.13% and 38.81% respectively for each equipment. Finally, the Pareto Diagram was performed and the main failures found through the FMEA were discussed. Therefore, this study is expected to contribute to the analysis of maintenance indicators in order to reduce equipment failures.